In Vitro Study on the Regulation of Annexin IV and VEGF by hCG in the Human Endometrium - Shaoyuan Xu; Jie Li; Xiaoyan Chen; Beiyu Liu (Biochemistry Research International)
Objective. Whether changes in vascular endothelial growth factor (VEGF) and annexin IV during implantation are regulated through the LH/hCG-R needs further research. To investigate the mechanism of hCG on the expression of annexin IV and VEGF in human endometrial cells. Methods. Endometrial cells were isolated and identified from human specimens. The proportion of glandular and epithelial cells was analyzed. Annexin IV and VEGF were analyzed by qRT-PCR (mRNA), western blot (proteins), and immunohistochemistry (proteins). Protein location was identified by immunohistochemistry. The cells were cultured with hCG, hCG/PD98059 (a MAPK inhibitor), or no treatment (control). Results. The proportions between the glandular epithelial cells and stromal cells at inoculation and when adding hCG were 25.8 ± 0.2% and 27.8 ± 0.04%, respectively (P>0.05). LH/hCG-R, annexin IV, and VEGF were found in the cytoplasm of endometrial cells. After 2, 6, 12, and 24 h of hCG treatment, compared with 1 h, VEGF mRNA was increased by 1.25-fold, 3.19-fold, 4.21-fold, and 4.86-fold and annexin IV by 2.23-fold, 3.37-fold, 5.14-fold, and 5.02-fold. Compared with the control group, annexin IV mRNA and protein were increased in the hCG and hCG/PD98059 groups (mRNA/protein: 1.99-fold/1.80-fold and 2.33-fold/1.93-fold, P<0.05). Compared with the control group, VEGF mRNA and protein were increased in the hCG group (mRNA/protein: 2.30-fold/1.86-fold), but not in the hCG/PD98059 group. Conclusion. hCG could upregulate the mRNA and protein expression of annexin IV and VEGF. The upregulation of annexin IV by hCG could not be inhibited by PD98059, but the upregulation of VEGF by hCG could.